Trail of the elephants - Russell, Geoff (Clayton South, Vic. : Distributed by Learning Essentials, 2003)
To create a new purpose built enclosure for the elephants at the Melbourne Zoo which would give visitors an experience of the animals and the cultural environment of their natural habitat, and provide for the unique housing requirements of the animals, was a collaborative exercise between specialist environmental designers and zoo staff. Examines how the project progressed, the personnel involved, and responses to the completed design.
Presenter: Geoff Russell.
Keywords: Elephants; Elephants -- Housing -- Design and construction; Zoos -- Australia -- Melbourne (Vic.) -- Design and construction